Production of a bioflocculant from Aspergillus niger using palm oil mill effluent as carbon source - Aljuboori, A.H.R. (Elsevier Ltd, 2014)
This study evaluated the potential of bioflocculant production from Aspergillus niger using palm oil mill effluent (POME) as carbon source. The bioflocculant named PM-5 produced by A. niger showed a good flocculating capability and flocculating rate of 76.8 to kaolin suspension could be achieved at 60h of culture time. Glutamic acid was the most favorable nitrogen source for A. niger in bioflocculant production at pH 6 and temperature 35Â°C. The chemical composition of purified PM-5 was mainly carbohydrate and protein with 66.8 and 31.4, respectively. Results showed the novel bioflocculant (PM-5) had high potential to treat river water from colloids and 63 of turbidity removal with the present of Ca2+ ion. Â© 2014 Elsevier Ltd.